Governing Diversity. Migrant Integration and Multiculturalism in North America and Europe - Adam, Ilke (European Studies, 2018)
During the 2000s, the European Union has witnessed a significant change in terms of integration policies for immigrants. Countries like Sweden and the Netherlands, who were both pioneers of multicultural policies in Europe both significantly limited such policies in the late 1990s.